Implementation of Gender-Responsive Teaching Methods among Secondary School Teaching Staff in Mafia District, Tanzania - Thabiti Hassan Thabiti; Baraka Mwandilawa; January Basela (Archives of Current Research International, 2023)
In regard to teaching career, there have been gender disparities in extent using of teaching methods and strategies among teaching staff in schools which ultimately constrain academic performance of students. The use of gender responsive teaching methods became among the strategies that can enhance the performance of students. The study aimed at assessing the extent use of gender responsive teaching methods (GRTM) among teaching staff in secondary schools in Mafia district, in Tanzania. The study was guided by the following research questions, the first research question was, to what extent do teachers use gender responsive teaching methods among teaching staff in secondary schools?, while second research question was, is there any relationship between students academic performance and gender responsive teaching methods used in the classroom?. The study adopted cross sectional research design using a sample of 249 respondents including 184 students and 65 teachers who were selected randomly. Data were collected through survey, interviews and focus group discussions. Qualitative data were analyzed using thematic analysis and quantitative data were analyzed by descriptive statistics analysis and inferential statistics (Chi-Square). The study found that, some of secondary teachers had moderate awareness on the use of GRTM in secondary schools particularly in class use of gender sensitive language with regard to what is taught, how teaching takes places, how and what is learned in the context of male and female students was high (Mean=6.08±1.833) and use of gender sensitive language used in a class was also high (Mean=4.98±1.833).The study also found that, there is significant association between students academic performance and the extent teachers ensuring that, working groups were mixed comprising male and female students was statistically significant at 5% with a chi square value of 14.48 and P= 0.025.Further, the study found that, there is positive significant association between students academic performance and teachers in encouraging both male and female students to present results in a group work had a chi square of 9.434 and P=0.151 It is concluded that, GRTM had significant influence on students’ academic performance in secondary schools in Tanzania. The study recommends that, education policy makers, curriculum planners, teachers, gender practitioners, NGO’s and CBO’s should provide pre-services and in-services teachers training on GRTM in order to increase uses so as to improve students’ teaching methods.